2017
DOI: 10.7150/jca.20480
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin -- a promising biomarker for cancer therapy

Abstract: Osteopontin (OPN), a multifunctional protein, has emerged as a potentially valuable biomarker for diagnosing and treating cancers. Recent research focuses on its involvement in tumor biology including the cell proliferation, survival, angiogenesis, invasion, and metastasis. Understanding the molecular mechanisms and pharmacological effects of OPN in cancer development could lead to new targets for improving cancer diagnosis and treatment.This review explains how the structurally conserved domains of OPN are as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
119
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(124 citation statements)
references
References 97 publications
2
119
0
3
Order By: Relevance
“…A number of genes are recognized to contain functional vitamin D response elements, which also include OPN . Survival from colorectal cancer has been reported to be positively associated with vitamin D status and OPN expression level, respectively . The potential effect of calcitriol on OPN gene signature in colorectal cancer development warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of genes are recognized to contain functional vitamin D response elements, which also include OPN . Survival from colorectal cancer has been reported to be positively associated with vitamin D status and OPN expression level, respectively . The potential effect of calcitriol on OPN gene signature in colorectal cancer development warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The potential correlation between KRAS and other oncogene remains to be further investigated. Osteopontin (OPN) is a 34 kD integrin‐binding glycophosphoprotein, which plays an important role in cancer progression and is considered as a potential biomarker for cancer prognosis . It is encoded by SPP1 gene that has five isoform variants, which include OPN‐a, OPN‐b, OPN‐c, isoform 4 and isoform 5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, stage I, manifests a good prognosis, in contrast to stages II, III, and IV. Thus, the current staging system is inadequate to predict outcome of treatment, which strongly recommends that the find of prognostic significance of molecular alterations in gastric cancer, such as osteopontin, human epidermal growth factor receptor type 2(HER2), fibroblast growth factor receptor 2 (FGFR2), programmed death‐ligand 1 (PD‐L1), epithelial cell adhesion molecule (EpCAM) . Additionally, the rapid development of molecular biology techniques such as transcriptome sequencing and high‐throughput DNA microarrays facilitate molecular analysis of gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Another study revealed that OPN promotes tumor cell invasion of hepatocellular carcinoma by activating MMP-9 through the NF-κB signaling pathway (12). Additionally, OPN and MMP-9 are considered biomarkers for monitoring cancer progression (11,15,16). OPN is also a biomarker for microglial activation and brain injury (17).…”
Section: Introductionmentioning
confidence: 99%